Feasibility for utilizing IEEE 802.15.4 compliant radios inside rotating electrical machines for wireless condition monitoring applications - Sampath Kumar, Padmanabhan (2020)
The conventional condition monitoring systems for rotating electrical machines are predominantly based on externally available signals, while the internal signals, especially on the rotor, remain relatively unexplored. To access these internal signals, wireless sensors offer an effective solution in terms of cost and ease of deployment. However, the environment inside an electrical machine deviates from a typical wireless RF application and communication link reliability under such scenarios needs to be assessed. This paper explores the feasibility of utilizing the ubiquitous IEEE 802.15.4-2.4 GHz compliant radios for wireless sensor deployment inside an electrical machine. A series of measurements are made to experimentally investigate the link quality characteristics under the prominent environmental factors such as the multipath effect, Doppler shift, magnetic field interference, and shielding effect of the enclosure. Packet reception rate, received signal strength and link quality indicator are used as the metrics to quantify the link performance. It is observed that contrary to popular belief, the link quality between nodes inside the machine is not deteriorated and in fact is found to be enhanced. A poor link quality is observed for the connection between nodes placed inside and outside the machine. Moreover, the link quality is highly dependent on spatial position and prone to interference. However, a sufficiently stable link can be established at the expense of high transmit power. These experimental findings indicate that wireless RF-based sensor nodes can be deployed inside an electrical machine and it opens an opportunity to explore invasive condition monitoring systems.